High‐Temperature CsxC58 Fullerides. Issue 3 (23rd November 2018) - Ulas, Seyithan; Weippert, Jürgen; Malik, Sharali; Strelnikov, Dmitry; Kern, Bastian; Amati, Matteo; Gregoratti, Luca; Kiskinova, Maya; Böttcher, Artur
Abstract : Cs doped non‐IPR fullerides (IPR: isolated pentagon rule) have been grown by co‐depositing C58 cations and Cs atoms on highly oriented pyrolytic graphite (HOPG). The C58 cages, as building blocks of the material, form a predominantly covalently stabilized scaffold, C58 –C58, which is doped by Cs atoms thermally diffusing across the bulk. The heating of the solid Csx C58 sample is accompanied by sublimation of Cs, C58, and C60 species from the topmost layers of the sample. However, the major part (>94%) of the material survives the heating procedure and constitutes a doped high‐temperature carbon solid, HT‐Csx C58 . The new non‐IPR material exhibits surprisingly high thermal stability. It survives a heating flash up to 1100 K at which the classic IPR‐Csx C60 phase does not exist anymore. However, the thermally treated HT‐Csx C58 phase exhibits a considerably depleted Cs content ( x  < 2) and a significantly modified carbon scaffold. The apparent stability of the scaffold results from covalent C–C bonds interlinking adjacent carbon cages. Cs atoms in the HT‐Csx C58 phase contribute to this stability only as minority species, forming comparably weak ionic bonds with C58 –C58 oligomers. However, this interaction facilitates the formation of structural defects (new non‐IPR sites) in carbon cages. The surface topography of the HT‐Csx C58 as monitored by scanning photoemission microscopy, atomic force microscopy, and scanning electron microscopy is governed by islands standing out by their elevated Cs/C ratio. Abstract : The properties of macroscopic films comprising the non‐IPR fulleride Csx C58 are described: Cs catalyzes the thermally activated transfer of C2 units between fullerene cages thus leading to a new phase, HT‐Csx C58 . This work describes the electronic and vibrational properties of this new phase and presents an analysis of chemical inhomogeneities mirrored by spectral photoemission microscopy.